Penerapan Problem Based Learning untuk Meningkatkan Kemampuan Analisis Pelajaran PAI pada Siswa SMK Pesantren Darul Dakwah - Lintang Nur Feka; Nur Fitria Ningsih; Justsinta Sindi Alivi (Jurnal Budi Pekerti Agama Islam, 2025)
The purpose of this study is to see how the application of the problem-based learning (PBL) model can help students analyze Islamic Religious Education (PAI) lessons at SMK Pesantren Darul Dakwah. PBL is used to teach students to think critically, analytically, and find solutions to religious problems. This study used a qualitative approach with a classroom action research (PTK) design, which was conducted in two cycles. The results showed that PBL can help students analyze PAI materials. This was evident by the observation results which showed better task assessment, and more active and critical student participation in group discussions. This research proposes a wider application of PBL model in Islamic Education learning in SMK to improve students' understanding and analysis skills in the context of religious learning.